Electrolyte plasma polishing solution and polishing process for titanium alloy
By using an electrolyte plasma polishing solution composed of ammonium chloride, ammonium fluoride and potassium fluoride, combined with appropriate process parameters, the problem of limited effects of titanium alloy materials in electrolyte plasma polishing technology is solved, and efficient surface material removal and finish improvement is achieved.
Patent Information
- Application Number
- CN202411976607.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing electrolyte plasma polishing technology has limited application effects on titanium alloy materials, and the polishing mechanism is unclear, making it difficult to achieve efficient surface material removal and surface finish improvement.
An electrolyte plasma polishing solution of titanium alloy is used, including ammonium chloride, ammonium fluoride and potassium fluoride. By adjusting the ratio of the electrolyte and polishing process parameters, such as working voltage, temperature and time, a near-neutral fluorine salt electrolyte is formed to improve the polishing efficiency of titanium alloy workpieces.
The surface roughness of titanium alloy workpieces is significantly reduced, from Sa 1.1758μm to Sa 0.1-0.3μm, improving the surface finish and polishing quality, while reducing environmental pollution and worker operating risks.
Smart Images

Figure CN119776836A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polishing liquid, and in particular relates to an electrolyte plasma polishing liquid and a polishing process for titanium alloy. Background Art
[0002] Ti-6Al-4V is an α+β dual-phase titanium alloy. Due to its excellent comprehensive properties, it has been widely used in aerospace, defense, biomedicine and other fields. Especially in the biomedical field, Ti 6-Al-4V alloy is used to manufacture bone implants, joint prostheses, artificial heart valves, etc. due to its low density, high strength-to-weight ratio, low elastic modulus, corrosion resistance, and excellent biocompatibility. However, titanium alloys exhibit low thermal conductivity and high chemical reactivity, which brings challenges during processing, such as increased cutting temperature, susceptibility to processing rebound and surface hardening. Titanium alloy parts are often processed by precision casting, CNC milling, additive manufacturing, etc., leaving processing defects such as high roughness, multiple remelting layers, and uneven residual stress distribution on the surface, affecting the performance. In addition, post-processing, such as spraying hydroxyapatite coating on some biomedical components, requires a high-quality substrate surface. Therefore, polishing is often required to improve the surface quality and service life of the components.
[0003] Electrolyte plasma polishing is an innovative metal surface treatment technology that combines anodic dissolution and plasma chemical treatment. During the processing, the workpiece is immersed in a low-concentration inorganic salt-based electrolyte at a specific temperature. A gas film layer that wraps the workpiece is formed on the surface of the workpiece by applying DC high voltage. The local high voltage breaks through the gas film layer, resulting in plasma generation. An oxide film is formed on the anode surface under the action of plasma-enhanced electrochemical oxidation, and then the oxide film is peeled off through complex physical and chemical processes such as discharge bombardment, electrochemical dissolution and plasma discharge erosion. The dynamic balance between oxide film formation and peeling achieves material removal and surface polishing of the workpiece. Compared with polishing methods such as electrochemical and mechanical polishing, electrolyte plasma polishing has the advantages of no structural selectivity, no macroscopic force, high processing efficiency, good polishing quality, and environmental friendliness. It is particularly suitable for polishing biomedical parts with free-form surfaces or complex geometries, such as knee joints, dental implants and surgical instruments. It can not only be used as the final processing procedure of biomedical parts, but also as a pretreatment for processing processes such as thermal spraying, ion implantation, physical vapor deposition, and chemical vapor deposition. It has broad application prospects in the biomedical field. However, based on the current research status at home and abroad, it can be seen that electrolyte plasma polishing technology has been widely studied in stainless steel materials, and its related polishing mechanism, process parameters and surface properties have been deeply studied, and it has been relatively maturely applied. For the polishing of valve metal materials such as titanium alloys, its polishing mechanism is still unclear, and the polishing effect that can be achieved by electrolyte plasma polishing technology is currently limited. Summary of the invention
[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes an electrolyte plasma polishing liquid and a polishing process for titanium alloy.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] The invention provides an electrolyte plasma polishing liquid for titanium alloy. The polishing liquid comprises the following components in parts by weight: 1.5-3 parts of ammonium chloride, 1.25-2.75 parts of ammonium fluoride, 0.75-4.65 parts of potassium fluoride and 89-97 parts of a solvent.
[0007] Furthermore, the solvent is pure water.
[0008] The present invention provides a polishing process using the titanium alloy electrolyte plasma polishing liquid, comprising the following steps:
[0009] (1) Mix the components in claim 1 and dissolve them in deionized water, stir them evenly to obtain the electrolyte plasma polishing liquid of the titanium alloy, put the electrolyte plasma polishing liquid of the titanium alloy into a stainless steel polishing tank, and set the heating temperature of the steam generator and the polishing operation time;
[0010] (2) The titanium alloy workpiece to be polished is fixed on the anode rod and connected to the positive pole of the power supply, and the stainless steel polishing tank is connected to the negative pole of the power supply. Then, the titanium alloy workpiece to be polished is immersed in the electrolyte plasma polishing liquid of the titanium alloy to perform the electrolyte plasma polishing operation.
[0011] Furthermore, the heating temperature in step (1) is 80-95°C.
[0012] Furthermore, the polishing operation time in step (1) is 1-30 minutes.
[0013] Furthermore, the power supply in step (2) is a DC voltage of 280-350V, and the peak current is less than 200A.
[0014] Furthermore, in step (2), the titanium alloy workpiece to be polished is immersed in the polishing liquid at a speed of 10-40 cm / min, and the top of the titanium alloy workpiece to be polished is located 5-15 cm below the liquid surface.
[0015] Furthermore, the polishing process also includes post-processing, the specific steps of which are: using anhydrous ethanol and deionized water to ultrasonically clean the workpiece, and then drying it.
[0016] Furthermore, the titanium alloy workpiece to be polished is Ti-6A l-4V of GB / T3620.1-2007 standard.
[0017] The invention also provides a titanium alloy workpiece, which is processed by the polishing process.
[0018] The Ti-6Al-4V titanium alloy workpiece of GB / T3620.1-2007 standard is processed by the above-mentioned polishing process, and the surface roughness of the titanium alloy workpiece is reduced from Sa 1.1758μm to Sa 0.1-0.3μm.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The titanium alloy electrolyte plasma polishing liquid described in the present invention includes ammonium chloride, ammonium fluoride and potassium fluoride. Ammonium fluoride forms a highly stable complex with the titanium alloy workpiece, which can be tightly adsorbed on the surface of the titanium alloy workpiece to inhibit the formation of an oxide film on the surface of the substrate. At the same time, ammonium chloride as an electrolyte can increase the oxidation rate of the titanium alloy workpiece in the oxidation stage and improve the overall polishing efficiency. Ammonium fluoride and potassium fluoride as complexing agents not only increase the fluoride ion concentration, but also enhance their complexing effect and make it easier to form soluble fluorides. Secondly, the near-neutral fluoride salt electrolyte obtained by mixing ammonium fluoride, potassium fluoride and ammonium chloride helps to dissolve the oxide film on the surface of the titanium alloy workpiece. This chemical action can cooperate with the surface gas layer discharge plasma bombardment to achieve the removal of surface materials of titanium alloy workpieces with complex shapes and structures.
[0021] The electrolyte plasma polishing liquid for titanium alloy described in the present invention is formulated with a near-neutral fluoride salt electrolyte. As the working voltage and temperature continue to increase to 280V and 90°C, the energy input increases, the VGE thickens and gradually stabilizes, the sample surface is constantly in contact with and separated from the polishing liquid during the reaction, plasma discharge and electrochemical dissolution reaction proceed simultaneously, the oxide film removal rate and generation rate gradually balance, and uniform material removal is achieved on the workpiece surface. When the electrolyte plasma polishing operation is performed for 7 minutes, the peak and trough difference of the sample surface profile is reduced, the material surface becomes smooth, and a better polishing effect is achieved.
[0022] Compared with traditional electrochemical polishing, the use of low-concentration inorganic salt solution instead of high-concentration inorganic acid solution reduces environmental pollution and protects the workers' working environment.
[0023] Compared with traditional mechanical polishing, electrolyte plasma polishing is less dependent on workers, has high polishing efficiency and causes less damage to the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the surface roughness (Sa 1.1758 μm) of a titanium alloy workpiece before electrolyte plasma polishing according to an embodiment of the present invention;
[0025] Figure 2 Schematic diagram of the surface roughness (Sa0.1001 μm) of the titanium alloy workpiece after electrolyte plasma polishing according to Example 1 of the present invention;
[0026] Figure 3 This is a surface morphology image of the titanium alloy workpiece after electrolyte plasma polishing described in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0028] The present invention is described in detail below in conjunction with the embodiments.
[0029] Example 1
[0030] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0031] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water and stirred to obtain a polishing liquid, wherein the mass concentration of ammonium chloride in the polishing liquid is 1.5%, the mass concentration of ammonium fluoride is 2.75%, and the mass concentration of potassium fluoride is 4.65% (the concentrations recorded hereinafter are all mass concentrations, mass concentration = solute mass / total solution mass × 100%);
[0032] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 90°C and the polishing operation time to 7 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 280 V between the cathode and the anode, and a peak current of 9 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min at 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0033] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0034] from Figure 1-3 It can be seen that the surface finish is significantly improved by the electrolyte plasma polishing liquid and its preparation method, and the surface roughness is reduced from Sa 1.1758μm to Sa0.1001μm.
[0035] Example 2
[0036] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0037] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water, and stirred to obtain a polishing liquid, wherein the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 4.65%;
[0038] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 80°C and the polishing operation time to 3 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 240 V between the cathode and the anode, and a peak current of 13 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0039] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0040] Example 3
[0041] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0042] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water, and stirred to obtain a polishing liquid, wherein the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 4.65%;
[0043] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 95°C and the polishing operation time to 15 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 350 V between the cathode and the anode, and a peak current of 7 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0044] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0045] Example 4
[0046] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0047] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water and stirred to obtain a polishing liquid, wherein the concentration of ammonium chloride in the polishing liquid is 3%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 4.65%;
[0048] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 90°C and the polishing operation time to 7 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 280 V between the cathode and the anode, and a peak current of 9 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min at 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0049] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0050] Example 5
[0051] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0052] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water and stirred to obtain a polishing liquid, wherein the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 1.25%, and the concentration of potassium fluoride is 4.65%;
[0053] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 90°C and the polishing operation time to 7 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 280 V between the cathode and the anode, and a peak current of 9 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min at 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0054] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0055] Example 6
[0056] An electrolyte plasma polishing liquid for titanium alloy and a preparation method thereof, comprising the following steps:
[0057] (1) Preparation of electrolyte plasma polishing liquid: ammonium chloride, ammonium fluoride and potassium fluoride are dissolved in pure water, and stirred to obtain a polishing liquid, wherein the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 0.75%;
[0058] (2) dissolving the obtained polishing liquid in a polishing tank, setting the heating temperature of the steam generator to 90°C and the polishing operation time to 7 min, fixing the titanium alloy workpiece to be polished on the anode rod and connecting it to the positive electrode of the power supply, connecting the stainless steel polishing tank to the negative electrode of the power supply, applying a DC voltage of 280 V between the cathode and the anode, and a peak current of 9 A, and then immersing the titanium alloy workpiece to be polished at a descent speed of 10 cm / min at 10 cm below the liquid surface of the electrolyte plasma polishing liquid to perform electrolyte plasma polishing operation;
[0059] (3) The titanium alloy workpiece after electrolyte plasma polishing was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes, then placed in deionized water for ultrasonic cleaning for another 15 minutes, and placed in a drying oven for drying and sample packaging.
[0060] Comparative Example 1
[0061] The only difference from Example 1 is that the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of titanium tetrafluoride is 4.65%.
[0062] Comparative Example 2
[0063] The only difference from Example 1 is that the concentration of tetraethylammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of titanium tetrafluoride is 4.65%.
[0064] Comparative Example 3
[0065] The only difference from Example 1 is that the concentration of ammonium chloride in the polishing liquid is 5%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 4.65%.
[0066] Comparative Example 4
[0067] The only difference from Example 1 is that the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 0.5%, and the concentration of potassium fluoride is 4.65%.
[0068] Comparative Example 5
[0069] The only difference from Example 1 is that the concentration of ammonium chloride in the polishing liquid is 1.5%, the concentration of ammonium fluoride is 2.75%, and the concentration of potassium fluoride is 6%.
[0070] Comparative Example 6
[0071] The only difference from Example 1 is that the concentration of ammonium chloride in the polishing liquid is 1.5%, and the concentration of ammonium fluoride is 2.75%.
[0072] Comparative Example 7
[0073] The only difference from Example 1 is that the concentration of ammonium fluoride in the polishing liquid is 2.75%, and the concentration of potassium fluoride is 4.65%.
[0074] Comparative Example 8
[0075] The only difference from Example 1 is that the heating temperature of the steam generator is 70°C.
[0076] Comparative Example 9
[0077] The only difference from Example 1 is that a DC voltage of 150V is applied between the cathode and the anode.
[0078] The titanium alloy workpieces obtained by different electrolyte plasma polishing processes in Examples 1-6 and the titanium alloy workpieces obtained by different electrolyte plasma polishing solutions in Comparative Examples 1-9 were subjected to surface roughness tests. The test results are shown in Table 1.
[0079] Table 1 Results
[0080] Voltage (V) Temperature(℃) Time (min) Roughness Sa(μm) Example 1 280 90 7 0.1001 Example 2 240 80 3 0.4571 Example 3 350 95 15 0.2873 Example 4 280 90 7 0.6468 Example 5 280 90 7 0.5424 Example 6 280 90 7 0.4539 Comparative Example 1 280 90 7 0.4357 Comparative Example 2 280 90 7 0.6254 Comparative Example 3 280 90 7 0.9474 Comparative Example 4 280 90 7 0.6591 Comparative Example 5 280 90 7 0.5732 Comparative Example 6 280 90 7 1.2167 Comparative Example 7 280 90 7 0.9854 Comparative Example 8 280 70 7 0.3528 Comparative Example 9 150 90 7 1.0758
[0081] As shown in Table 1, the present invention explores the influence of key factors such as electrolyte ratio, working voltage, polishing liquid temperature, and polishing time on the surface roughness of CT4 titanium alloy during electrolyte plasma polishing. The experimental results show that: (1) When the working voltage is too low or too high, the polishing effect of the CT4 titanium alloy sample is poor. When the working voltage is 280V, the surface roughness of the sample can be reduced to about 0.1μm, and the surface morphology is uniform. (2) As the polishing liquid temperature increases, the surface roughness of the CT4 titanium alloy sample decreases. (4) As the polishing time increases, the surface roughness of the CT4 titanium alloy sample remains basically unchanged after it is reduced to a certain limit. (5) The electrolyte polishing liquid with an ammonium chloride concentration of 1.5%, an ammonium fluoride concentration of 2.75%, and a potassium fluoride concentration of 4.65% is the optimal solution ratio. The near-neutral fluoride electrolyte obtained helps dissolve the oxide film on the surface of the titanium alloy workpiece.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte plasma polishing liquid for titanium alloy, characterized in that: The polishing liquid comprises the following components in parts by weight: 1.5-3 parts of ammonium chloride, 1.25-2.75 parts of ammonium fluoride, 0.75-4.65 parts of potassium fluoride and 89-97 parts of solvent.
2. The electrolyte plasma polishing liquid for titanium alloy according to claim 1, characterized in that: The solvent is pure water.
3. A polishing process using the electrolyte plasma polishing liquid of titanium alloy according to claim 1, characterized in that: The steps include: (1) Mix the components in claim 1 and dissolve them in deionized water, stir them evenly to obtain the electrolyte plasma polishing liquid of the titanium alloy, put the electrolyte plasma polishing liquid of the titanium alloy into a stainless steel polishing tank, and set the heating temperature of the steam generator and the polishing operation time; (2) The titanium alloy workpiece to be polished is fixed on the anode rod and connected to the positive pole of the power supply, and the stainless steel polishing tank is connected to the negative pole of the power supply. Then, the titanium alloy workpiece to be polished is immersed in the electrolyte plasma polishing liquid of the titanium alloy to perform the electrolyte plasma polishing operation.
4. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: The heating temperature in step (1) is 80-95°C.
5. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: The polishing operation time in the step (1) is 1-30 minutes.
6. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: The power supply in step (2) is a DC voltage of 280-350V, and the peak current is less than 200A.
7. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: In the step (2), the titanium alloy workpiece to be polished is immersed in the polishing liquid at a speed of 10-40 cm / min, and the top of the titanium alloy workpiece to be polished is located 5-15 cm below the liquid surface.
8. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: The polishing process also includes post-processing, the specific steps of which are: using anhydrous ethanol and deionized water to ultrasonically clean the workpiece, and then drying it.
9. The polishing process of the titanium alloy electrolyte plasma polishing liquid according to claim 3, characterized in that: The titanium alloy workpiece to be polished is Ti-6Al-4V of GB / T3620.1-2007 standard.
10. A titanium alloy workpiece, characterized in that: The workpiece is processed by the polishing process described in any one of claims 3-9.